Accelerating SDGs to Alleviate Poverty: Synergy Between National Amil Zakat Agency (BAZNAS) and Islamic Financial Institutions (IFI) - Retnowati, May Shinta; Yusuf, M. Asror; Cahyani, Meitria; Hidayat, Iman Nur; Al Faruqi, Musta’an (University of Darusssalam Gontor, 2024)
The low level of progress in poverty alleviation in Indonesia is the responsibility of all elements of society. To achieve the realization of the success of the Sustainable Development Goals (SDGs) in 2030, it must be able to be realized. This is not limited to achieving rather than a target but also a need of each country. Through the collaboration of the National Amil Zakat Agency (BAZNAS) and Islamic Financial Institutions (IFI), it has great potential in realizing the goals of the SDGs to eradicate poverty. This type of research is qualitative with descriptive analysis. The results of the study show that Islamic financial institutions can function as potential partners of BAZNAS in providing a zakat collection platform that is easily accessible to the public. With the integration of Islamic financial services, such as internet banking and mobile banking, customers can easily distribute their zakat, infaq, and shadaqah through IFI.